2017
DOI: 10.1186/s12888-016-1185-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the validation of the Chinese Mandarin version of the Social Responsiveness Scale in a Mainland China child population

Abstract: BackgroundResearchers from several different countries have found the Social Responsiveness Scale (SRS) to have good psychometric properties. However, to our knowledge, no studies on this subject have been reported in Mainland China. In this study, we investigated the psychometric properties of the Chinese Mandarin version of the SRS when used in Mainland China.MethodsThe reliability and validity of the parent-report SRS in a sample of 749 children of 4- to 14-year-olds: 411 typically developing and 338 clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 48 publications
5
60
0
Order By: Relevance
“…These results are consistent with the findings in previous studies based on UK and Japanese samples [Auyeung et al, 2008;Wakabayashi et al, 2007]. Similar results were also reported in study using other instruments, for instance, the SRS [Cen et al, 2017]. A significant and positive correlation was found between the scores of the Chinese-AQ-Girls and age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the findings in previous studies based on UK and Japanese samples [Auyeung et al, 2008;Wakabayashi et al, 2007]. Similar results were also reported in study using other instruments, for instance, the SRS [Cen et al, 2017]. A significant and positive correlation was found between the scores of the Chinese-AQ-Girls and age.…”
Section: Discussionsupporting
confidence: 93%
“…Each item is rated on 4‐point Likert scale, with total scores ranging from 0 to 195 (the higher score indicating more autistic traits). A previous study has found that the reliability and validity for Mandarin Chinese version of SRS were satisfactory to good (Cronbach's α = 0.89), supporting it as a reliable instrument for children in mainland China [Cen et al, ].…”
Section: Methodsmentioning
confidence: 97%
“…Symptoms of the children with ASD were assessed with the Autism Behavior Checklist (ABC) [14], Social Responsiveness Scale (SRS) [15]and the CARS test. Higher scores of ABC, CARS, and SRS scores indicate more serious autistic symptoms.…”
Section: Subjectsmentioning
confidence: 99%
“…Subjects aged 4 to 10 years in the dataset were selected. The Social Responsiveness Scale (SRS) was used as a complementary diagnostic test in the study, and a total raw score of 56.5 was set as the cutoff score [22]. Subjects who scored above 56.5 in the control group and scored below 56.5 in the case group were excluded.…”
Section: Subjectsmentioning
confidence: 99%